Assessment of the risk of falling with the use of timed up and go test in the elderly with lower extremity osteoarthritis - Zasadzka, Ewa (Clin Interv Aging, 2015)
BACKGROUND: Falling in the elderly results in a significant number of admissions to hospitals and long-term care facilities, especially among patients with lower extremity osteoarthritis (OA). OBJECTIVE: The aim of the study was to assess the risk of falling in adults older than 60 years with OA using timed up and go (TUG) test. MATERIALS AND METHODS: A total of 187 patients (aged >60 years) were enrolled in the study. The assessment included: basic activities of daily living (ADLs), lower extremity strength with the use of the 30-second chair stand test (30 CST), and assessment of the risk of falling (TUG test). Pain intensity was evaluated with the numeric rating scale (NRS). RESULTS: The TUG test results were significantly better in younger OA patients (aged 60–69 years), as compared with their older peers (aged 70–79 years; P<0.01) and the oldest group (aged >80 years; P<0.001). Also, the 30 CST results were significantly higher in younger OA patients (P<0.05). Subjects older than 80 years had a significantly worse ADL score (P<0.05 and P<0.001). Pain complaints were reported significantly more frequently by women than men (P<0.05). A correlation between age and the TUG test score (r=0.412; P<0.0004) as well as between the TUG test and the 30 CST scores (r=0.7368; P=0.000) was detected. In the group with the TUG test score of <13.5 seconds, the 30 CST (P<0.0001) and ADL (P<0.003) results were significantly better. A comparison of fallers vs nonfallers revealed that the number of falls was significantly higher in the group of subjects who scored ≥13.5 when compared to <13.5 (P=0.003). Fallers significantly more often reported pain (P<0.0001), whereas nonfallers had significantly better 30 CST results (P=0.0003). CONCLUSION: Elderly population with OA is at an elevated risk of falling, which increases with progressing age, pain, and muscle weakness. It seems prudent to identify individuals at a high risk of falling and to propose an adequate treatment for them.